2006
DOI: 10.1111/j.1399-3046.2006.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of adverse events in outpatient pediatric renal allograft biopsies

Abstract: In 1999, our center implemented a policy of outpatient protocol biopsies as standard practice for the clinical management of pediatric renal allograft recipients. In order to determine the safety of this procedure, we conducted a retrospective chart audit of all outpatient renal allograft biopsies performed at our center. Biopsies were performed under conscious (midazolam) or procedural (propofol/fentanyl) sedation. Localization of the lower pole of the renal allograft was achieved with renal ultrasound. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 30 publications
3
38
0
Order By: Relevance
“…Similar findings in native renal biopsies were also reported from a large Brazilian cohort (Piotto et al, 2008). As such, Birk et al (Birk et al, 2007) hypothesized that the slightly higher incidence of post-biopsy gross hematuria (8.4%) in their cohort of 43 renal transplant recipients compared to previously published reports (1.9-3.5%) was their use of a larger 16-G needle compared to an 18-G needle used elsewhere. With regards to other factors, several retrospective analyses have shown no significant difference in complication rates whether the biopsy was performed as an outpatient or inpatient procedure (Hussain et al, 2003(Hussain et al, , 2010Simckes et al, 2000), under general anesthesia or sedation (Durkan et al, 2006;Hussain et al, 2010;Webb et al, 1994), by a supervised trainee or by an attending physician or consultant (Durkan et al, 2006;Simckes et al, 2000), and between an intraperitoneal and extraperitoneal graft in the case of allograft percutaneous biopsies (Vidhun et al, 2003).…”
Section: Minor Complications Major Complicationssupporting
confidence: 76%
See 4 more Smart Citations
“…Similar findings in native renal biopsies were also reported from a large Brazilian cohort (Piotto et al, 2008). As such, Birk et al (Birk et al, 2007) hypothesized that the slightly higher incidence of post-biopsy gross hematuria (8.4%) in their cohort of 43 renal transplant recipients compared to previously published reports (1.9-3.5%) was their use of a larger 16-G needle compared to an 18-G needle used elsewhere. With regards to other factors, several retrospective analyses have shown no significant difference in complication rates whether the biopsy was performed as an outpatient or inpatient procedure (Hussain et al, 2003(Hussain et al, , 2010Simckes et al, 2000), under general anesthesia or sedation (Durkan et al, 2006;Hussain et al, 2010;Webb et al, 1994), by a supervised trainee or by an attending physician or consultant (Durkan et al, 2006;Simckes et al, 2000), and between an intraperitoneal and extraperitoneal graft in the case of allograft percutaneous biopsies (Vidhun et al, 2003).…”
Section: Minor Complications Major Complicationssupporting
confidence: 76%
“…In rare cases of children with serious contraindication or objection to sedation or anesthesia, ''verbal sedation'' has been used, with the child talked through the procedure with the help of a child life specialist trained in this approach (Hussain et al, 2003). Case series from North American centers show that general anesthesia is most often reserved for infants or very small children where lack of cooperation during the procedure is a concern as well as in children whose airways may be at risk with sedation alone (Birk et al, 2007;Simckes et al, 2000;Sweeney et al, 2006). This approach is not necessarily the case worldwide and, in fact, a recent audit in the United Kingdom (Hussain et al, 2010) showed 6 of 11 centers routinely using general anesthesia for pediatric kidney biopsies.…”
Section: Nuts and Bolts: Sedation Or Anesthesia For The Pediatric Renmentioning
confidence: 99%
See 3 more Smart Citations